Predictive Capability of an iPad-Based Medical Device (medx) for the Diagnosis of Vertigo and Dizziness - Feil, Katharina; Feuerecker, Regina; Goldschagg, Nicolina; Strobl, Ralf; Brandt, Thomas; von Müller, Albrecht; Grill, Eva; Strupp, Michael (Frontiers in Neurology, 2018)
Background:Making the correct diagnosis of patients presenting with vertigo and dizziness in clinical practice is often challenging. Objective:In this study we analyzed the usage of the iPad based program medx in the prediction of different clinical vertigo and dizziness diagnoses . We examined the power of medx to distinguish between different vertigo diagnoses. Patients and methods:The data collection was done in the outpatient clinic of the German Center of Vertigo and Balance Disorders. The “gold standard diagnosis” was defined as the clinical diagnosis of the specialist during the visit of the patient standardized history and clinical examination. Another independent and blinded physician finalized each patient’s case in constellatory diagnostic of medx by entering all available clinical information in the system. The accuracy, sensitivity, specificity as well as positive and negative predictive values for the most common diagnoses were determined. Sixteen possible different vertigo and dizziness diagnoses could be provided by medx constellatory diagnostic system. These diagnoses were compared to the “gold standard” by retrospective review of the charts of the patients over the study period. Results:610 patients (mean age58.1±16.3 years, 51.2% female) were included. The accuracy for the most common diagnoses was between 82.1- 96.6% with a sensitivity from 40- 80.5% and a specificity of more than 80%. When analyzing the quality of medx in a multiclass-problem for the six most common clinical diagnoses the sensitivity, specificity, positive and negative predictive value were as follows: Bilateral vestibulopathy (81.6%, 97.1%, 71.1%, 97.5%), Menière's disease (77.8%, 97.6%, 87.%, 95.3%), benign paroxysmal positional vertigo (61.7%, 98.3%, 86.6%, 93.4%), downbeat nystagmus syndrome (69.6%, 97.7%, 71.1%, 97.5%), vestibular migraine (34.7%, 97.8%, 76.1%, 88.3%) and phobic postural vertigo (80.5%, 82,5%, 52.5%, 94.6%), Conclusions:This study demonstrates that medx is a new and easy approach to screen for different diagnoses. With the high specificity and high negative predictive value the system helps to rule out differential diagnoses and can therefore also lead to a cost reduction in health care system. However, the sensitivity was unexpectedly low, especially for vestibular migraine. All in all, this device can only be a complementary tool, in particular for non-experts in the field.